Effects of Pelargonium sidoides (UMCA ®) on pulmonary contusion from blunt thoracic trauma in rats (Annals of Medical Research, 2021)
Aim: The aim of the present study was to evaluate the effect of Pelargonium sidoides (UMCA ®) which was antibacterial, antiviral, anti-inflammatory and antioxidant, on pulmonary contusion (PC) caused by isolated blunt thoracic trauma (BTT) in an experimental rat model.Material and Methods: A total of 24 rats were divided into three groups: control group (CG), sham group (SG), and Pelargonium sidoidesgroup (PSG). PC was induced by isolated BTT for all the groups except the control group. Pelargonium sidoidestreatment was performed by gavage for 72 hours to the PSG after truma. Blood and tissue samples were collected from the groups. Malondialdehyde (MDA), superoxide dismutase (SOD),glutathione (GSH) and arterial blood gas parameters were measured. Lung tissue samples were collected for histopathology.Results: Histopathologically, alveolar congestion, hemorrhage,edema,disruption and neutrophil infiltrationwere significantly higher in SG when compared with CG(p0.001, p=0.007, p=0.040, p=0.003, p=0.001). Leukocyte infiltration was significantly decreased in PSG when compared with SG (p=0.025). Biochemically, MDA level was significantly higher in SG than in CG (p0.001) and GSH level was significantly lower in SG than in CG (p0.001). MDA level was significantly lower in PSG than in SG (p=0.002). In blood gas parameters PH and PO2 level was significantly higher in PSG than in SG (p=0.013, p0.001) and PCO2 level was significantly lower in PSG than in SG (p0.001).Conclusion: PS prevents further injury by decreasing leukocyte infiltration,MDAand regulating ventilation -perfusion in lung contusions. PS may have a role in the progression of inflammation but not in preventing the pathologic disruption of pulmonary parenchyma exactly.